Parental education and exposure of female and male students to bulling in school environment - Polovina Nada; Đerić Ivana (Temida, 2009)
The paper presents the results of research exploring the correlation between exposure of elementary school students to various types of bulling at school (stealing of personal belongings, violence, coercion, mockery, shunning) and their parents' educational level. Special emphasis was put on connections in mother-daughter and father-son dyads were explored. The research is a part TIMSS 2007 International Project covered a representative sample of 2447 8th Grade students (1161 boys and 1286 girls) from 36 elementary schools in Serbia. A questionnaire was used to collect the information on assessment of school environment, as well as students' experience of peer victimization. Overall, 48.1% students (in male sub-sample 54.4%; in female sub-sample 42.7%) reported being subjected to some kind of bullying in the preceding month. Much more frequently than girls, boys were subjected to theft of personal belongings, coercion and shunning. Correlation is found between educational level of mothers and bullying of their daughters at schools (especially violence, coercion and mockery). While students/daughters of highly educated mothers were more frequently subjected to coercion (forced to do something they did not want to do), daughters of poorly educated mothers were more frequently subjected to shunning. The sub-sample of boys did not indicate any correlation between educational level of fathers and peer victimization in school environment.